2018
DOI: 10.1007/s13187-018-1386-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Health Education on Female Teachers’ Knowledge and Practices Regarding Early Breast Cancer Detection and Screening in the Jazan Area: a Quasi-Experimental Study

Abstract: Educational programs are important tools for breast cancer prevention. The purpose of this study was to assess the effectiveness of health education in improving the knowledge and practices of female teachers regarding screening tools and the early detection of breast cancer. A two-group quasi-experimental design was conducted among 150 female teachers, who were selected from 75 schools of the Jazan General Administration of Education. Schools were chosen by a simple cluster randomization method and non-random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…Such studies have incorporated certain women groups such as female university students, female workers, women attending health care centers, or female residents [12,[17][18][19][20]. Nevertheless, only a few studies have been conducted on female teachers regarding BCS practice in the world [11,[21][22][23][24][25]. For example, in Malaysia, even though a few studies have shed light on BCS practice among teachers, no research has been done on BCS practice among Yemeni female school teachers in Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies have incorporated certain women groups such as female university students, female workers, women attending health care centers, or female residents [12,[17][18][19][20]. Nevertheless, only a few studies have been conducted on female teachers regarding BCS practice in the world [11,[21][22][23][24][25]. For example, in Malaysia, even though a few studies have shed light on BCS practice among teachers, no research has been done on BCS practice among Yemeni female school teachers in Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…45 , 46 But Ahmadian et al 30 state that women who have mammograms have adequate information obtained from various sources. Alameer et al 67 indicated the education’s role in increasing women’s awareness and practice for early BC detection.…”
Section: Discussionmentioning
confidence: 99%
“…However, a percentage of the population surveyed is unaware of this and there is considerable ignorance about the age at which breast examination should start [32]. Other studies in young people mention that those who managed to acquire a level of awareness of risk factors and BC did not put this into practice in their daily life [28,[37][38][39].…”
Section: Discussionmentioning
confidence: 99%